Juridical Analysis of Judge's Decision in Criminal Case of Law with Threats of Violence Performed by Adults towards Adult Victims (Study of Decision No. 769/PID.B/2021/PN Rantauprapat) - Tri Windasari; M. Yusuf Siregar; Wahyu Simon Tampubolon (Budapest International Research and Critics University, 2022)
Obscenity is known as an act that leads to harassing a woman in public asdone to achieve self-satisfaction outside the bondmarriageso that it violates the rules of decency, obscene acts are subject to Article 290 of the Criminal Code which is punishable by a maximum imprisonment of 7 years.is any act of abuse of physical force with or without the use of means that is against the law and poses a danger to the body, life, and independence of people. The formulation of the problem in this matter is 1.What are the legal regulations regarding obscene acts with legally adult victims? 2. What are the legal considerations of the panel of judges in destroying cases of obscene acts in decision no. 769/pid.B/2021/PN rap? The method used in this writing is using the Juridical Normative Empirical method, which is conducting field research, namely to the Rantauprapat District Court with the interview method, to support the data the author needs, and also taking references from various books, legislation, articles, scientific essays, and other readings that are related to the problems discussed in the preparation of this article. The problem of obscene acts with threats of violence committed by adults against adults in which the article that regulates obscene acts contains article 289 of the Criminal Code concerning